Simplified calculation model for the effect of nonlinear temperature dependence of thermoelectric properties on the conversion efficiency. (1st April 2021) - Sui, Xiaomei; Zhang, Zhe; Zhang, Yuqi; Xu, Daochun; Li, Wenbin
Abstract: Thermoelectric (TE) materials play an important role in energy production and utilization, but the temperature dependence of material properties makes theoretical analysis challenging. In this work, the TE differential equation is solved by introducing the volume average of TE material parameters, and a simplified TE element model is established for a TE element with a linear temperature profile. The temperature dependence of the Seebeck coefficient, electrical resistivity and thermal conductivity are incorporated into the thermal conductivity equation, and the TE conversion efficiency is solved. This proposed model is applied to a high-performance N-type half-Heusler alloy, and the obtained maximum conversion efficiency agrees well with the numerical results (with relative error 1.36%) for an average temperature T m  = 510 K and temperature difference Δ T  = 440 K. The results confirm that the proposed model, which incorporates the Thomson effect, is simple and accurate, providing valuable guidance for optimal performance design of TE devices. Highlights: Putting volume average properties makes TE non-linear model to a linear one. Conversion efficiency of the proposed model agrees well with the numerical result. The effect of coefficients on η demonstrates the accuracy of the proposed model.